THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL CLIMATE ON EMPLOYEE ENGAGEMENT - Jhon Mart Ramadan; Erita Yuliasesti Diah Sari; Fatwa Tentama (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
Abstract This study aims to determine the effect of transformational leadership and organizational climate on employee engagement. The participants were active employees of 57 men and 49 women between age 22-42 years old representing each department. The instrument used is the employee engagement scale, transformational leadership scale, and organizational climate scale. The data analysis technique used is multiple regression analysis with SPSS 21.0 for windows. This study indicates that transformational leadership and organizational climate simultaneously and significantly affect employee engagement (p = 0.000; p < 0,01). Furthermore, transformational leadership has a positive influence on employee engagement (p = 0.005; p < 0,01) and organizational climate has a positive influence on employee engagement (p = 0.016; p < 0,05). This study shows that transformational leadership and organizational climate play a role in shaping employee engagement among employees. Employees have a greater chance of achieving engagement when they provide positive support, thus creating a conducive work environment. Keywords: employee engagement, transformational leadership, organizational climate